PERBANDINGAN EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH PADA PENDAPATAN ASLI DAERAH - Bhujangga, Oka Dhananjaya; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 13 No 1 (2015), 2015)
The purpose of this research is to ancover the effectiveness and the contribution of local taxes in the local revenue in the city of denpasar and badung district and to kno w the difference was the effectiveness and the contribution of local taxes on a local revenue in the city of Denpasar and district Badung 2009-2013. Based on the results analysis was known the ratio of the effectiveness of Denpasar to town and district Badung in tax revenues areas classified as very effective.An analysis of the contribution of local tax revenue in Denpasa r local revenue city and district years 2009-2013 Badung always fluctuating and the average level of the contribution of local tax and city D enpasar B adung district during the past five years in the category of very good.There is no difference in the ratio of the effectiveness of local tax revenue between the city and district Denpasar Badung 2009-2013, years but there were differences contribution tax receipts on a local revenue Denpasar between the city and district Badung 2009-2013.
Keywords: effectiveness, contribution, regional taxes, local revenue